Provision of Registration Services by Public Administration Agencies in the Field of Land Protection (Law and Safety, 2019)
The author of the article has stated that the land relations reform and the start of decentralization led to changes in the system of public administration agencies in the field of land protection and expanded their powers, for example, to provide registration services.The author has paid attention to the fact that the current Land Code of Ukraine (hereinafter referred to as the LC of Ukraine), in particular the Section VII “Administration in the field of land use and protection”, provides the execution of only management functions in the field of land protection by public administration agencies.It has been emphasized that there were no complex studies in Ukraine concerning theoretical and applied problems of legal regulation of service relations, in particular the provision of registration services, in the field of land protection with the participation of public administration agencies, which would be based on the current legislation.The author of the article has stated that the provision of services in the field of land protection is a new type of activity for public administration agencies in the field of land protection.Service legal relations ensure the realization of private and public interests and are formed in those areas of land use and protection management, where public and private land interests are interdependent. Thus, the owner is interested in fixing and publicly announcing his land rights in the field of state registration of land rights. But parties concerned cannot ensure their private interests without the assistance of the state. Thus, the state, represented by public administration agencies, guarantees that the state registration of land rights is in the interest of one and all.It has been noted that currently the legal regulation of service relations for the provision of registration services in the field of land protection has not been enshrined either in any general regulatory act, which is the Law of Ukraine “On Administrative Services” gated from September 6, 2012 No. 5203-VI, or in special regulatory acts, such as the LC of Ukraine and the Law of Ukraine “On Land Protection”. Such circumstances necessitate a change in the existing approaches to the legal regulation of service relations for the provision of registration services in the current legislation and to enshrine provisions for providing the registration services in the field of land protection by public administration agencies in the LC of Ukraine, namely in the Section VII “Administration in the field of land use and protection” and in the Law of Ukraine “On Land Protection”.
Keywords: provision of registration services; public administration agencies; land protection; administrative services; services